Spatiotemporal distribution and evolution pattern of Chinese Go League clubs in 20 years of professionalism - Kunlun, Chen; Xiaoqiong, Liu; Xu, Zhang; Lei, Ding (Frontiers in Sports and Active Living, 2023)
Chinese Go League has gradually grown and matured in the two decades from 1999 to 2018 and becomes an important aspect for the urban sports culture. This paper explores the spatio-temporal distribution pattern and diffusive evolution characteristics of Chinese Go League clubs from the perspective of sports geography, by using the methods of mathematical statistics, spatio-temporal trajectory and geospatial analysis. This research finds that: (1) the number of Chinese Go League clubs shows a trend of “stepped” increase over the past two decades, and there is much room for further growth; (2) the distribution of Chinese Go League clubs varies greatly in different cities, mainly in municipalities directly under the central government and provincial capital cities (accounting for 82.6% of the total), and forming a spatial pattern of Bohai Rim, Yangtze River Delta and Southwest region of China; (3) the distribution of host cities of Chinese Go League clubs is generally discrete, with clustering and random distribution only in individual years, and the spatial distribution tends towards southern cities; (4) the names and host cities of Chinese Go League clubs change frequently, with diverse types of relationships with host cities, which mainly includes: urban stability, urban transition and urban fluctuation. In the future, the professionalization and sustainable development of Chinese Go industry can be enhanced by the marketability of Chinese Go clubs, developing new markets for Chinese Go, and building a healthy development model with multiple linkages of Chinese Go clubs, sponsors and host cities.